Evaluasi Program Layanan Bimbingan Karir dengan Model Kirkpatrick di SMK Negeri 1 Kecamatan Guguak Kabupaten Lima Puluh Kota - Yasmiri Yasmiri; Nurhasan Syah; Ambiyar Ambiyar; Mustofa Abi Hamid (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
Career guidance is expected to help students to establish students career choice to be a professional in the future. However, current conditions and the fact in the area is not as expected. This study aimed to evaluate how Reaction, Learning, Behavior, and Result on the Career Guidance program at SMK Negeri 1 Kecamatan Guguak Kabupaten Lima Puluh Kota. The kind of this research is an evaluation study with the program evaluation of Kirkpatrick model that is a Reaction component, Learning, Behavior, and Result. The method used is a mixed method. Quantitative data were collected through questionnaire, while the qualitative data collected through interview, observation, and documentation. It can be concluded that career guidance services at SMK Negeri 1 Kecamatan Guguak Kabupaten Lima Puluh Kota is good enough category, Reaction and Learning component still needs to be improved and more attention.